0763 The Impact Of Medications On Sleep In The Lab For Children With ADHD. (27th April 2018) - Hoosier, T; Gregory, L; Paasch, V; Ewen, J; Lam, J
Abstract: Introduction: Children with ADHD have a higher prevalence of sleep problems: prolonged sleep latency, increased night wakings, and restlessness. Stimulant medications are known to increase sleep difficulty while non-stimulant medications (alpha-agonists) are known to improve sleep. Some published studies indicate that parents overestimate sleep difficulty based on actigraphy results. Very few studies have evaluated sleep in children with ADHD using polysomnography. We hypothesize that patients on stimulant medication will have more difficulty with sleep and patients on an alpha agonist would have less difficulty with sleep compared to patients not taking medication based on results from polysomnography. Methods: A retrospective chart review was performed on all children under 18 years of age with ADHD referred to our sleep lab in a one-year period, by child neurologists, child psychiatrists and developmental pediatricians. We obtained information on the patient's age, sex, sleep efficiency, sleep latency, and wakefulness after sleep onset (WASO). Analyses included regression modeling and scaled JZS Bayes factor analyses. Bayes factor analyses allow for greater certainty than traditional frequentist tests when establishing a lack of effect (i.e., accepting the null hypothesis). Results: Of the 69 children studied, 28 children were taking a stimulant, 8 were taking an alpha agonist, 9 were on both medications, and 24 were not on either. Bayes factor analyses report on the likelihood that the null hypothesis is correct (no difference in sleep parameters caused by medication), as compared to the likelihood of the alternative hypothesis (medications are associated with a difference in sleep parameters). Our data suggest no relationship between either medication and any sleep parameter. For stimulants, sleep efficiency Bayes factor was 2.9, WASO was 3.9, and sleep latency was 2.4. Regression modeling established no association between either medication and any sleep parameter, even when controlling for age and/or sex. Conclusion: Our data suggests that medication likely has no impact on sleep for children with ADHD in the lab. These findings are limited by the retrospective nature of the study. Support (If Any): None.